Towards a philosophy of real mathematics - Corfield, David (Cambridge University Press, 2003)
In this ambitious study, David Corfield sets out a variety of approaches to new thinking about the philosophy of mathematics, and challenges both philosophers and mathematicians to develop the broadest and richest philosophical resources for work in their disciplines.